IROND-L: study protocol for a French prospective, quasi-experimental, multicentre trial to examine the impact of a coordinated multidisciplinary approach for women victims of violence - Florence Bretelle; Marc Bardou; Inès Ben Ghezala; Marc Dommergues; Ghada Hatem; Fabienne El-Khoury; Pascale Hoffmann; Leila Yacini; Zohra Jaffal; Andre Soares; Sophie Duchesne; Sara Eudeline; et al. (BMJ Open)
Background and objectives Violence against women (VAW) is widespread and can have serious physical and mental health consequences, including post-traumatic stress disorder (PTSD) and sleep disorders. Victim-survivors often face barriers in accessing specialised care, highlighting the need for a multidisciplinary response, especially in healthcare settings. The Maison des Femmes (MdF) model provides holistic support to women experiencing VAW, including medical, psychological, social and legal support. The aim of this study is to examine whether the MdF’s comprehensive intervention programme offers advantages over standard care in improving mental health indicators, such as PTSD.Method and analysis Our pragmatic quasi-experimental study uses a non-randomised controlled cluster design. The intervention group comprises women enrolled in MdFs in five French cities, while the comparison group includes women receiving usual care in sociomedical structures located geographically close to MdF centres. Our study aims to recruit 360 women (180 per group), aged 18 years or older, who have experienced intimate partner violence or sexual violence and who seek care at the study centres. The primary analysis will compare the change in PTSD Checklist for DSM-5 (PCL-5) scores over 6 months in the two groups using multivariable linear regression with propensity score adjustment. Secondary outcomes include sleep disorders, quality of life, symptoms of anxiety and depression, self-esteem, sense of safety and well-being, initiation of legal and socioprofessional proceedings, and healthcare utilisation.Ethics and dissemination The study was approved by the ‘Comité de protection des personnes Ile de France III’ (CPP Committee for the Protection of Persons Ile de France III; institutional review board on 20 December 2023; Ref no. (Numéro SI): 23.04197.000491).The results of the study will be communicated via academic publications; easily understandable briefs for a broader public; and proactive involvement with medical institutions, journalists and advocacy groups.Trial registration number NCT06226818. Version Number 1- february2024.